2018
DOI: 10.1177/0333102418780426
|View full text |Cite
|
Sign up to set email alerts
|

Altered cortical excitability in persistent idiopathic facial pain

Abstract: NTC01746355.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…15 Recently, it was also suggested that PIFP might be associated with alterations in intracortical GABAergic modulation. 11 In line with the pathophysiological concept of a central pain component in patients with PIFP, we hypothesized that they would show alterations in trigeminal pain processing when contrasted against healthy controls (HC) and performed event-related brainstem functional magnetic resonance imaging (fMRI) using a wellestablished trigeminal nociceptive test paradigm. 24,26 It is noteworthy that intranasal ammonia as used in this experiment has an olfactory component shown in mice and that intranasal trigeminal stimulation…”
Section: (Criterion C 2 Of Pifp)mentioning
confidence: 99%
“…15 Recently, it was also suggested that PIFP might be associated with alterations in intracortical GABAergic modulation. 11 In line with the pathophysiological concept of a central pain component in patients with PIFP, we hypothesized that they would show alterations in trigeminal pain processing when contrasted against healthy controls (HC) and performed event-related brainstem functional magnetic resonance imaging (fMRI) using a wellestablished trigeminal nociceptive test paradigm. 24,26 It is noteworthy that intranasal ammonia as used in this experiment has an olfactory component shown in mice and that intranasal trigeminal stimulation…”
Section: (Criterion C 2 Of Pifp)mentioning
confidence: 99%
“…A recent study on PIFP patients using cortical excitability measurements by transcranial magnetic stimulation applied to the cortical representation of the masseter muscle of both hemispheres showed changes in in-tracortical modulation involving GABAergic mechanisms, which may be related to certain aspects of the pathophysiology of this chronic pain condition [12]. Significant disturbances in somatosensory function, also called "central sensitization", may explain the generalized dysfunction of the nociceptive system with imbalance between descending inhibitory and facilitatory mechanisms or deficiencies related to diffuse noxious control system [13]. Finally, some observations postulate that PIFP may involve a disproportionate response to mild injury, as occurs in patients with CRPS (Complex Regional Pain Syndrome), affected by traumatic injury and neuropathic response [14].…”
Section: Discussionmentioning
confidence: 99%
“…Of those, chronic pain has been one of the most debilitating conditions and appears to be inseparable for those who were diagnosed with Gulf War Illness 3 5 . While the pathophysiology underlying pain symptomology has not been well defined, it is well known that chronic pain states are associated with diminished intrinsic supraspinal pain modulatory function which often presents as reduced motor cortical excitability 6 10 . On the other hand, increased motor cortical excitability is known to be associated with enhanced pain inhibition 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, assessing the underlying motor cortical excitability in patients with GWI related diffuse body pain including headaches, muscle, and joint pain can offer a new level of understanding in the illness and potentially provide guidance for therapeutic intervention for this patient population. While it is widely accepted that chronic pain states can be associated with impaired corticomotor excitability represented by a diminished supraspinal modulatory state from traumatic or non-traumatic causes 6 8 , 12 14 , to the authors’ best knowledge, no study has been conducted to assess the corticomotor excitability in patients with GWI related chronic diffuse body pain including headaches, joint, and muscle pain.…”
Section: Introductionmentioning
confidence: 99%